Multiplier Effect of Religious Tourism for Income of the Surrounding Community in Banjar Regency - Asyahri, Yusuf; El Wafa, Faqih; Syaugi, Syaugi; Muhaimin, Muhaimin (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
This research departs from the development of religious tourism in Banjar Regency which has its own charm and is often visited by local, national and international tourists is the Tomb of Sheikh Muhammad Arysad Al-Banjari or known for his book essay, namely Sabilal Muhtadin and the Tomb of Guru Sekumpul who is a charismatic cleric his era so that the purpose of this study is to analyze the multiplier effecet of religious tourism on the income of the people in the Regency Banjar. The research method used is a quantitative approach, then sampling using cluster sampling and quota sampling. In relation to the quota sampling technique, a sample of 40 respondents consisting of business actors, workers and the community was determined, while the sampling cluster was at Datu Kalampayan Tomb and Guru Sekumpul Cemetery. Data collection techniques using structured interviews and analyzed using descriptive statistics by adopting a formula from the multiplier effect known as Keynes' theory. The results showed that the value of Keynesian Local Income Multiplier, Ratio Income Multiplier has a value of >1 both Type I and II so that it has an impact on the economic development of the community.